Justification of the Kinematic Diagrams for the Distribution System of a Planetary Hydraulic Motor - Voloshina, Angela; Panchenko, Anatolii; Boltynskiy, Oleg; Panchenko, Igor; Titova, Olena (International Journal of Engineering and Technology, 2018)
The output characteristics of a planetary (orbital) hydraulic motor could be significantly improved if the kinematic diagrams for its working fluid distribution system are chosen correctly and substantiated. Fluctuations in the flow of the power fluid cause pulsation in the cavity of the input pressure of the hydraulic motor. This results to vibration of the hydraulic system elements. Thus, the hydraulic motor can be considered as a source of pulsation which leads to functional failures of the hydraulic system. As they run at low rotational speeds with high torque, planetary hydraulic motors are commonly applied for a hydraulic drive in active working tools of self-propelled machinery. It has been established that one of the main components of a planetary hydraulic motor, which causes pressure pulsations, is its distribution system. The frequency and amplitude of these pulsations depends on the kinematic diagram for the distribution system of the power fluid. Therefore, we studied how the kinematic diagram for the distribution system effects on the output characteristics of a planetary motor. Since the change in the capacity of a distribution system with various kinematic diagrams influences on the output characteristics of a planetary motor, the impact was investigated. The kinematic diagrams, which improve the output characteristics of planetary hydraulic motors, were justified.Â